2003
DOI: 10.1002/cphc.200300907
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved Second Harmonic Generation Near‐Field Scanning Optical Microscopy

Abstract: Novel scanning probe microscopy (SPM) spectroscopic techniques are currently receiving much attention. The increasing number of spectroscopic techniques, when combined with the high spatial resolution that is attainable with SPM, makes it possible to probe a large range of material characteristics on the nanoscopic scale. The ability to probe samples on the nanoscale with femtosecond time resolution promises to increase our knowledge of nanoscale electronic devices and their dynamics.Several time-resolved spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…48 We note that photoinduced changes in χ (2) in other materials have been attributed to carrier-induced modulations without associated structural modifications. 32,39,54 However, the 2−3 ps time scale observed here is inconsistent with an effect like this which would be expected to occur on instrument-limited time scales. Moreover, we also observe similar effects using pump and probe beams at 340 and 1030 nm, respectively, with 500 fs pulse width, indicating that the observed changes are not driven by nonthermal effects associated with nonequilibrium carrier densities but rather by the total energy absorbed by the nanowire (see Supporting Information).…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…48 We note that photoinduced changes in χ (2) in other materials have been attributed to carrier-induced modulations without associated structural modifications. 32,39,54 However, the 2−3 ps time scale observed here is inconsistent with an effect like this which would be expected to occur on instrument-limited time scales. Moreover, we also observe similar effects using pump and probe beams at 340 and 1030 nm, respectively, with 500 fs pulse width, indicating that the observed changes are not driven by nonthermal effects associated with nonequilibrium carrier densities but rather by the total energy absorbed by the nanowire (see Supporting Information).…”
contrasting
confidence: 88%
“…Optical trapping enables manipulation of single nanostructures in three dimensions and characterization of their optical properties. Nanowires with high aspect ratios tend to be aligned along the optical axis of the trapping beam in the trap. , Nonlinear second harmonic generation (SHG) techniques allow one to probe the structural symmetry of the nanowire and associated carrier relaxation dynamics , as encoded in the second-order nonlinear optical susceptibility (χ (2) ), sensitive to the deviation from centrosymmetry within the crystallographic unit cell, without being influenced by substrate effects. Upon photoexcitation, incident photons are coupled into one end of a nanowire and waveguided along the nanowire length, with the fundamental generating the second harmonic along the length of the nanowire …”
mentioning
confidence: 99%
“…The term η may also be a function of carrier density due to exciton interaction effects, as has been previously suggested; however, it is difficult to decouple this effect from a change in β. Previous studies on transient SHG using relatively low pump fluence have shown that the for a highly noncentrosymmetric material can be considerably lowered by pumping free carriers from the valence band to the conduction band . These excited carriers then no longer contribute to the intrinsically large χ (2) of the equilibrated material, probably because of the symmetry-breaking associated with excitation to further delocalized states.…”
mentioning
confidence: 99%
“…Previous studies on transient SHG using relatively low pump fluence have shown that the χ eff (2) for a highly noncentrosymmetric material can be considerably lowered by pumping free carriers from the valence band to the conduction band. 22 These excited carriers then no longer contribute to the intrinsically large χ (2) of the equilibrated material, probably because of the symmetry-breaking associated with excitation to further delocalized states. As the carriers relax to the "ground-state" configuration, the χ (2) value recovers.…”
mentioning
confidence: 99%
See 1 more Smart Citation